Archaeology of Early Colonial Interaction at El Chorro de Maíta, Cuba - Valcárcel Rojas, Roberto, 1968- (Book collections on Project MUSE., 2016)
This work enables scholars to examine how the encomienda labor draft worked in the hinterlands, without the everyday presence of Spanish overlords or priests. It allows not only the first opportunity to bring the key research at El Chorro to the attention of the international scholarly community, adding a new dimension to our understanding of the encomienda system, but also to reveal the earliest moments of the hybrid Cuban culture that persists today.